The Role of External Aid in Ghana's Library Development - Alemna, A.A. (Library Review, 1992)
Examines the roles played by various international and government organizations in the development of libraries in Ghana. Argues some justification for the continued reliance on external assistance in Ghana′s library development, despite the controversial nature of such assistance. Concludes that all government efforts should be made to supplement external assistance in the development of libraries in Ghana.
Research Article
Keywords: Agencies; funding; Ghana; libraries